Comparative analysis of reactions to visual and auditory stimuli in research on EEG evoked potentials - Tyburcy, Łukasz; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2018)
The paper describes results of comparison of reactions times to visual and auditory stimuli using EEG evoked potentials. Two experiments were used to applied. The first one explored reaction times to visual stimulus and the second one to auditory stimulus. After conducting an analysis of data, received results enable determining that visual stimuli evoke faster reactions than auditory stimuli.